Comparative Study of Contact Repulsion in Control and Mutant Macrophages Using a Novel Interaction Detection - José Alonso Solís-Lemus; Besaiz J Sánchez-Sánchez; Stefania Marcotti; Mubarik Burki; Brian Stramer; Constantino Carlos Reyes-Aldasoro (Journal of Imaging, 2020)
In this paper, a novel method for interaction detection is presented to compare the contact dynamics of macrophages in the Drosophila embryo. The study is carried out by a framework called macrosight, which analyses the movement and interaction of migrating macrophages. The framework incorporates a segmentation and tracking algorithm into analysing the motion characteristics of cells after contact. In this particular study, the interactions between cells is characterised in the case of control embryos and Shot mutants, a candidate protein that is hypothesised to regulate contact dynamics between migrating cells. Statistical significance between control and mutant cells was found when comparing the direction of motion after contact in specific conditions. Such discoveries provide insights for future developments in combining biological experiments with computational analysis.